Iot Based Stolen Vehicle Monitoring System - R.Jeya, C.Rajesbabu, Jaskeerat Singh, Akshit Singh (International Journal of Advanced Science and Technology, 2020)
The current transportation system is not ready to adapt to the growing problem of stolen vehicles. This paper aims to propose a stolen vehicle monitoring system that uses vehicle-mounted RFID tags for STOLEN VEHICLE DETECTION. This paper uses a technique to take care of the issue of stolen vehicles using a database of the last known location of the vehicle and cross-reference the owner’s information present in the system. Our system provides an easy platform to improve the maintenance of the database of stolen vehicles that the management system gathers. This information from various traffic light intersections is collected and problem area lanes are red-lit in case of a stolen vehicle is detected using an RFID tag reader. The Arduino board is connected to a GSM module which will be used to establish a connection to the local server where the database will be hosted from. The final information of the vehicle will be sent to the owner and the concerned authorities.